2020
DOI: 10.1108/aia-04-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Online training for physical activity practitioners on evidence-based practices for clients with autism

Abstract: Purpose Physical activity professionals often lack the experience and knowledge to implement the pedagogical and behavioral strategies required to successfully work with people with autism spectrum disorder (ASD). To enable individuals with ASD to achieve the benefits of exercise, physical activity professionals must be knowledgeable and skilled in relation to delivering evidence-based practices (EBP). The recent worldwide coronavirus disease pandemic highlights the value and necessity of effective online lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A study of the ACSM/Exercise Connection Autism Exercise Specialist Certificate’s online modules found that the frequency at which participants reported using evidence-based practices increased significantly from pretest to posttest (3.26 ± 0.59 to 3.40 ± 0.59; Cohen’s d = 0.15; P = 0.031). Moreover, participants perceived self-efficacy in using evidence-based practices significantly improved from pretest to posttest (2.78 ± 0.76 to 3.20 ± 0.76; Cohen’s d = 0.40; P < 0.001) (23).…”
Section: Delivering Exercise Requires a Visual Program (David)mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the ACSM/Exercise Connection Autism Exercise Specialist Certificate’s online modules found that the frequency at which participants reported using evidence-based practices increased significantly from pretest to posttest (3.26 ± 0.59 to 3.40 ± 0.59; Cohen’s d = 0.15; P = 0.031). Moreover, participants perceived self-efficacy in using evidence-based practices significantly improved from pretest to posttest (2.78 ± 0.76 to 3.20 ± 0.76; Cohen’s d = 0.40; P < 0.001) (23).…”
Section: Delivering Exercise Requires a Visual Program (David)mentioning
confidence: 99%
“…Although the education system may not be giving PE and APE teachers the education they need, the ACSM/Exercise Connection Autism Exercise Specialist Certificate may serve as an excellent educational adjunct. A recent study of the certificate’s online modules found that 20.9% of participants were adapted physical educators, and 26.7% were general physical educators (23).…”
Section: Awareness Raises More Questions Education Provides the Answe...mentioning
confidence: 99%